Strengthening Moderation and Arousing Students' Interest in Literacy at SDN Banjiran as Provision for the Future - Dzikri Muhammad; Tina Nur Aini; Gita Fitria Rusbaningrum; Hafidh Abrar Albar; Nafila Nariswari; Anisa Putri Nur Fadillah; Alif Nur Fadzilah (Universitas Palangka Raya, 2024)
Literacy is an activity that is useful for increasing information, knowledge, and insight. If children are trained and accustomed to reading from an early age, then the character of liking to read will grow in the child. Therefore, the KKN UIN Walisongo Semarang Team held a socialization of strengthening religious moderation and strengthening literacy interest at SDN Banjiran. Where the purpose of this socialization was carried out to provide a deep understanding to teachers and students regarding the importance of religious literacy in forming good and religious children's characters. Religious moderation literacy is the ability to understand, interpret and apply religious teachings in a balanced and tolerant way. Religious moderation literacy also includes the ability to communicate effectively about the values of moderation and to live side by side harmoniously with individuals from various religious backgrounds. In this socialization, learning media such as videos, material summaries in the form of power points and also educational applications are used to convey the values of religious moderation